Criminological Review of the Influence of Kameko Drink on Juvenile Perpetrators of Assault Crimes - Saharuddin, Saharuddin; Rahim, Abdul Jabar; Kamaruddin, Kamaruddin (Fakultas Syariah INSURI Ponorogo, 2023)
The aim of this research is to determine the factors influencing children's consumption of Kameko drink in the legal jurisdiction of Kulisusu sector and to determine the efforts of the Kulisusu sector police in preventing the circulation of Kameko drink among children. The approach method used in this study are using several approaches as whole unities, which are statute approach, case approach, and conceptual approach The research was conducted in the Kulisusu sector police area. The data sources consist of primary data supported by secondary data. Data collection techniques used were interviews and observations. The analysis technique used is qualitative descriptive method. The results of this research show that the factors influencing children's consumption of Kameko drink in the legal jurisdiction of Kulisusu sector can be grouped into determining factors and supporting factors. consuming alcohol makes children unable to focus on school, disrupt their studies, experience memory or memory problems, and increase the risk of suicide. Efforts made to combat the circulation of Kameko drink in the legal jurisdiction of Kulisusu sector include preventive and repressive measures.